2008
DOI: 10.1002/adsc.200700533
|View full text |Cite
|
Sign up to set email alerts
|

Palladium/Phosphite or Phosphate Catalyzed Oxidative Coupling of Arylboronic Acids with Alkynes to Produce 1,4‐Diaryl‐1,3‐butadienes

Abstract: Abstract:The intermolecular oxidative coupling of arylboronic acids with internal alkynes efficiently proceeds in a 2:2 manner in the presence of palladium acetate, a triaryl phosphite or phosphate, and silver carbonate as catalyst, ligand, and oxidant, respectively, to produce the corresponding 1,4-diaryl-1,3-butadiene derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…1,1,2,3,4,4-Hexaphenyl-1,3-butadiene ( 5 ) [ 62 ]: To the reaction mixture containing 4a , CuCl (1 mmol) and TCQ (2 mmol) were added. The reaction mixture was stirred for 12 h at room temperature and compound 5 was isolated in 43% yield.…”
Section: Methodsmentioning
confidence: 99%
“…1,1,2,3,4,4-Hexaphenyl-1,3-butadiene ( 5 ) [ 62 ]: To the reaction mixture containing 4a , CuCl (1 mmol) and TCQ (2 mmol) were added. The reaction mixture was stirred for 12 h at room temperature and compound 5 was isolated in 43% yield.…”
Section: Methodsmentioning
confidence: 99%
“…Satoh et al [14] demonstrated that the coupling reactions of aryl boronic acids with alkynes can be performed with palladium catalyst to give multiarylated butadienes. Miura et al [15] optimized the process to produce 1,4-diaryl-1,3-butadienes by adding triaryl phosphate, but the product yields were still moderate due to the facile deactivation of the palladium catalyst under the oxidative conditions. Based on the above, we propose that the combination of CuCl and palladium catalyst may promote the formation of two sp 2 C-sp 2 C ---A c c e p t e d M a n u s c r i p t bonds which will offer bis-arylated-1,3-butadienes.…”
Section: Introductionmentioning
confidence: 99%
“…Tetraarylethene is one of aggregation‐induced emission (AIE) active molecules which have shown numerous applications in biological probes and imaging, chemical sensing, optoelectronics, and stimuli‐response materials [22] . On the other hand, Miura and Satoh and coworkers developed the synthesis of 1,3‐butadiene derivatives from the reaction of internal alkynes with arylboronic acids ( Scheme 1 ,a ) [23,24] . Although AIE active 1,1,2,3,4,4‐hexaaryl‐1,3‐butadienes and their polymers have been also synthesized using Miura ’s method, [25–31] applications are limited probably because the reaction temperature is too high (120 °C) and because some 1,1,2,3,4,4‐hexaaryl‐1,3‐butadienes can easily be cyclized to produce 1,1,2,3,4‐pentaarylated dihydronaphthalenes [32] .…”
Section: Introductionmentioning
confidence: 99%